EH Domain-Containing 2 Deficiency Restricts Adipose Tissue Expansion and Impairs Lipolysis in Primary Inguinal Adipocytes - Fryklund, Claes; Morén, Björn; Shah, Shrenika; Grossi, Mario; Degerman, Eva; Matthaeus, Claudia; Stenkula, Karin G. (Frontiers in Physiology, 2021)
Lipid uptake can be facilitated via caveolae, specific plasma membrane invaginations abundantly expressed in adipocytes. The dynamin-related protein EH domain-containing 2 (EHD2) stabilizes caveolae at the cell surface. Here, we have examined the importance of EHD2 for lipid handling using primary adipocytes isolated from EHD2 knockout (Ehd2−/−) C57BL6/N mice. Following high-fat diet (HFD) feeding, we found a clear impairment of epididymal, but not inguinal, adipose tissue expansion in Ehd2−/− compared with Ehd2+/+ (WT) mice. Cell size distribution analysis revealed that Ehd2−/− mice had a lower proportion of small adipocytes, and an accumulation of medium-sized adipocytes in both epididymal and inguinal adipose tissue. Further, PPARγ activity, FABP4 and caveolin-1 expression were decreased in adipocytes isolated from Ehd2−/− mice. Inguinal adipocytes isolated from Ehd2−/− mice displayed reduced lipolysis in response to beta adrenergic receptor agonist, which was associated with reduced phosphorylation of perilipin-1 and hormone sensitive lipase (HSL). This impairment could not be rescued using a cAMP analog, indicating that impaired lipolysis in Ehd2−/− primary adipocytes likely occurs at the level of, or downstream of, protein kinase A (PKA). Altogether, these findings pinpoint the importance of EHD2 for maintained intracellular lipid metabolism, and emphasize differences in mechanisms regulating lipid handling in various adipose-tissue depots.